Mosque Da'wah Program and Muslim Youth: Study on Management of Saba Baduy Program in Banten - M Faturohim; Ahmad Faiz Khudlari Thoha; Fathurrahman Masrukan (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
The creative da'wah programs of mosques will be a strong attraction for their congregation. Saba Baduy is one creative program hold by the Muslim Youth of Masjid Agung Ar Rahman Pandeglang that combines da'wah and cultural values. This study aims to examine the planning process of the Saba Baduy program so that a comprehensive pattern of the program can be drawn. This study used a qualitative method. The data were collected through interviews and document studies. The results of this study found that there are four key success factors of the program planning: determining program goals and targets, planning for locations and transportation systems, preparing creative events, as well as security and comfort services for participants. In addition to these aspects, the right way of communication with the Baduy ethnic during the program is also an essential supporting factor. The impact of this study will be beneficial in the development of other creative da'wah programs in various mosques in Indonesia.